Evaluation of The Antidiarrheal Activity of Aqueous Stem Bark Extract of Anogeissus leiocarpus on Castor Oil-Induced Diarrhea in Rats - Ahmed, Maryam Usman; Emmanuel, Comfort; Adamu, Yusuf Muhammad (African Journal of Medicine, Surgery and Public Health Research, 2025)
Diarrheal diseases are a major public health problem in developing countries. Anogeissus leiocarpus is used in Africa and particularly in Nigeria for the empirical treatment of diarrhea. The present study was undertaken to evaluate the effects of aqueous stem bark extract of Anogeissus leiocarpus on castor oil-induced diarrhea in rats. Thirty (30) Wistar rats of both sexes were grouped into six groups (the first three of which served as the normal control, negative control and standard treatment respectively, the last three were used as test groups) of five rats per group. Diarrhea was induced by administering 1 ml/rat of castor oil orally. Phytochemical screening of the aqueous stem bark extract of Anogeissus leiocarpus revealed the presence of alkaloids, flavonoids, steroids, tannins, saponins and phenols. Treatment with the extract produced a significant dose-dependent inhibition of diarrhea. The percentage inhibition of diarrhea increased with corresponding increase in dose of the extract and was comparable with the percentage inhibition produced by the standard drug (loperamide). Treatment with this extract also produced a modest dose-dependent reduction on intestinal transit in rats and a statistically significant (p<0.05) dose-dependent reduction in the volume of intestinal content when compared with the negative control group. The results obtained from this study suggests that the aqueous stem bark extract of Anogeissus leiocarpus have significant antidiarrheal effect on animal models and this finding supports the traditional use of the plant extract in the management of diarrhea.